Implications of the World Health Organization (WHO) regulations concerning the sales of breast milk substitutes and country-specific indicators per the diamond location theory: A multi-country analysis - Mabilane, Bongile (University of Pretoria, 2024)
Dissertation (MPhil)--University of Pretoria, 2023